ANALISIS PROFITABILITAS, LEVERAG ANALISIS PROFITABILITAS, LEVERAGE DAN KEPEMILIKAN ASING TERHADAP CORPORATE SOCIAL RESPONSIBILITY (CSR) - Nur Fitri Eka Asbarini; Slamet Haryono (Program Studi Akuntansi Fakultas Ekonomi Universitas Sarjanawiyata Tamansiswa, 2021)
The purpose of this research is to determine the effect of profitabiliy , leverage variables, and foreign ownership on Corporate Social Responsibility (CSR). The type of research used is secondary data. The number of companies used as samples in the study was 10 manufacturing companies listed on the Indonesia Stock Exchange (BEI) for the 2015-2019 period using panel data analysis. The result showed that the profitability variable was proxies by Return On Assets, Return On Equity, the results showed that the Return On Equity variable affected on CSR disclosure, while Return on Assets did not effect. The leverage variable proxies by the Debt Equity Ratio and foreign ownership variable does not effect on CSR disclosure.